Fertility evaluation of rubber growing soils of Meghalaya - Singh KP; Chaudhuri D; Joseph Mercykutty; Thapliyal AP (Rubber Science, 2013)
Soil samples collected at two depths (0-30 and 30-60 cm) from the rubber growing areas of Meghalaya were analysed for availale nutrient status. The organic carbon (OC) content ranged from 5.7 to 21.6 g kg-1 and the mean value was 11.7 g kg-1. Highest OC content was recorded in West Garo Hills and lowest in South Garo Hills. In the entire Meghalaya state, 79.40 per cent of soil samples were recorded OC content in the medium range. The nutrient index value for organic carbon for the state as a whole was 1.99 indicating medium range of organic carbon status. Availability phosphorus (P) was very low for all the districts and the lowest in South Garo Hills (1.79 kg ha-1). Majority of the samples from all the districts where rubber is cultivated have shown low available and nutrient index values ranged from 1.00 to 1.02 and the fertility rating for available potassium (K) content of the rubber growing soils of Meghalaya was observed. The available K ranged from 1.92 to 2.10. fertility rating for available K content was found to be medium for the entire rubber growing soils of Meghalaya. The soil pH ranged from extremely acidic (3.97) to moderately acid (pH 5.41) and 64 per cent soil samples recorded pH between 4.5 to 5.
Keywords: Available nutrients; Available nutrients; Organic carbon; Organic carbon; Rubber; Rubber; Soil fertility; Soil fertility